DEVELOPMENT OF COLLAGEN-CONTAINING DRINKS - Y. Verkhivker; O. Myroshnichenko; S. Pavlenko (Harčova Nauka ì Tehnologìâ, 2021)
The problem of human aging is very relevant today. The mechanisms of aging are closely related to the decrease of such a protein substance as collagen in the human body. One of the possibilities for restoration the amount of this vital component is the use of collagen-containing juice products of everyday use in the diet. Taking into account the relevance and prospects of this issue, the direction of further work has been chosen accordingly. The purpose of the research is the use of collagen in the formulation of an assortment of juice products based on fruit and vegetable raw materials. To achieve the goal of the study we formulated the tasks that allowed us to research the range and quality indicators of different types of collagen of plant and animal origin (tomato, beef, pork and fish) as well as to justify the choice of the most preferred collagen sample for drinks. We have determined the optimal amount of this biologically active additive to ensure the required quality of the finished product. We have investigated the preservation of the active properties of various types of collagen in fruit and vegetable drinks. As a result of the studies performed it has been shown that beef collagen is the most acceptable and retains its active properties in an amount of 5% to the mass of the drink; it adds salt, alcohol, alkaline protein fractions according to its fractional composition. It has been shown that the amino acids methionine, tryptophan and hydroxyproline which confirm the presence of collagen in the product are contained in ready-made juice drinks enriched with collagen of beef origin. The formulations of fruit and vegetable drinks with the addition of collagen have been developed accordingly. A comparison of the organoleptic and physicochemical characteristics of finished drinks with the requirements of normative and technical documentation (DSTU 4283-2007) was carried out and their full compliance was proved.